2003
DOI: 10.1128/mcb.23.18.6618-6630.2003
|View full text |Cite
|
Sign up to set email alerts
|

PSF Acts through the Human Immunodeficiency Virus Type 1 mRNA Instability Elements To Regulate Virus Expression

Abstract: Human immunodeficiency virus type 1 (HIV) gag/pol and env mRNAs contain cis-acting regulatory elements (INS) that impair stability, nucleocytoplasmic transport, and translation by unknown mechanisms. This downregulation can be counteracted by the viral Rev protein, resulting in efficient export and expression of these mRNAs. Here, we show that the INS region in HIV-1 gag mRNA is a high-affinity ligand of p54nrb/PSF, a heterodimeric transcription/splicing factor. Both subunits bound INS RNA in vitro with simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
149
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(151 citation statements)
references
References 66 publications
(70 reference statements)
2
149
0
Order By: Relevance
“…40 Lastly, PSF has been shown to repress the expression of HIV-1 gag/pol and env mRNAs through cis-acting instability elements (INS) that target degradation. 41 Previously, we showed that PSF and p54 nrb interact with U5 snRNA. 23 During further analysis of this interaction by immunoprecipitation (IP) with PSF-specific antibodies, we show here that all five U snRNPs co-IP with PSF when HeLa nuclear extracts are adjusted to splicing conditions, regardless of the addition of pre-mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…40 Lastly, PSF has been shown to repress the expression of HIV-1 gag/pol and env mRNAs through cis-acting instability elements (INS) that target degradation. 41 Previously, we showed that PSF and p54 nrb interact with U5 snRNA. 23 During further analysis of this interaction by immunoprecipitation (IP) with PSF-specific antibodies, we show here that all five U snRNPs co-IP with PSF when HeLa nuclear extracts are adjusted to splicing conditions, regardless of the addition of pre-mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that PSF and NonO interact with the HIV-1 gag cis-acting instability elements (INS) and that overexpression of PSF, but not NonO, inhibits HIV-1 Gag p24 production in transfected HEK293 cells. 25 This study suggests that PSF and NonO may regulate HIV-1 mRNA production causing diminished HIV-1 gag-pol and env gene expression. 25 NonO has also been shown to form a complex with PSF and participate in the nonhomologous end-joining pathway, capable of DNA double-strand break rejoining.…”
Section: Introductionmentioning
confidence: 99%
“…25 This study suggests that PSF and NonO may regulate HIV-1 mRNA production causing diminished HIV-1 gag-pol and env gene expression. 25 NonO has also been shown to form a complex with PSF and participate in the nonhomologous end-joining pathway, capable of DNA double-strand break rejoining. 26 We thus speculated that NonO might have a role in the assembly of PICs and integration of the HIV-1 genome into the host chromosome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it binds PTB1, non-POU-domain-containing octamer-binding protein (NONO), and cell division cycle 5-like (CDC5L). In addition, SFPQ is involved in the pathogenic pathway of influenza virus and human immunodeficiency virus (LanderasBueno et al, 2011;Zolotukhin et al, 2003). Especially, SFPQ forms splicing factor-rich foci in a perinuclear pattern, related to the differentiation of myeloid cells (Shav-Tal et al, 2001).…”
Section: Sfpqmentioning
confidence: 99%